2022
DOI: 10.1186/s12889-022-14840-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of early marriage among married women in nine high fertility sub-Saharan African countries: a multilevel analysis of recent demographic and health surveys

Abstract: Background Early marriage is global issue that seriously harms women’s personal development and rights. Regarding this, information about married women’s early marriage is inadequate in the world, including sub-Saharan Africa; therefore, this study aimed to assess the early marriage of women in the top nine highly fertile SSA countries. Methods Data for this study was obtained from the most recent Demographic and Health Surveys. A total weighted sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…As a result, 56.34% (95% CI: 51.34-61.34) of Ethiopians were found to have married before the age of 18. This result is in line with research from Mali (58.2%) [60] and Sub-Saharan Africa (55.11%) [61]. This may be due to the similar socioeconomic characteristics of the research locations.…”
Section: Plos Onesupporting
confidence: 90%
“…As a result, 56.34% (95% CI: 51.34-61.34) of Ethiopians were found to have married before the age of 18. This result is in line with research from Mali (58.2%) [60] and Sub-Saharan Africa (55.11%) [61]. This may be due to the similar socioeconomic characteristics of the research locations.…”
Section: Plos Onesupporting
confidence: 90%
“…The study found that the burden of disease was higher among younger pregnant women (20–29 years) in low-and low-middle SDI regions, whereas it was higher among older pregnant women (30–39 years) in high SDI regions. Females in low-and low-middle SDI regions tend to marry and have children at an early age, such as 44 and 39% of girls in South Asia and sub-Saharan Africa, respectively, who marry before the age of 18 years, and are chronically malnourished ( 22 ). Evidence has shown that chronic malnutrition delays physical maturation and prolongs the adolescent growth beyond the age of 20 years ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a previous study in Ethiopia ( 14 , 28 ). A study from SSA regions also revealed that early marriage among rural women was higher compared to that of urban women ( 12 ). This may be due to rural areas' higher levels of poverty, stronger social networks, poorer educational prospects, and greater adherence to traditional norms, which may all be directly related to the practice of child marriage.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the World Bank outlined that by 2030, four trillion dollars will be lost due to child marriage (2). Studies from different continents indicated that educational status, residence, income level, employment status, family size, knowledge about legal marital age, and parental decision-making about when to get married were the most important determinants of child marriage (8,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation